PENGARUH PENGGUNAAN METODE PEMBELAJARAN KOOPERATIF MODEL JIGSAW TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 4 BUKITTINGGI - Hendrisman Hendrisman (Program Studi Pendidikan Bahasa Indonesia, , Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mahaputra Muhammad Yamin, 2020)
This research is motivated by cooperative method of jigsaw model which is one of the learning method that can provide opportunity to lead to success in learning writing. This study aims to 1) Describe the Influence of Text Writing Skills Student Description of Class VII by Using Cooperative Learning Method Jigsaw Model. 2) Describe the Effect of Using Text Writing Skills of Student Description of Class VII by Using Conventional Method. 3) Describe the Effect of Using Cooperative Learning Method of Jigsaw Model on Text Writing Skill Description of Grade VII Student. The research method applied is experimental method. In this study two classes were used, ie experimental class given a set of treatment and control class were not treated. Data analysis shows that, jigsaw model cooperative learning method influences in learning to write text description in experiment class. This is evidenced by the increase in student scores, which at the time of prenting the mean / mean () is 70.08. After applying the cooperative learning method of jigsaw model in the learning process in this class, the students' learning outcomes increase at the time of pascates with the average value () 93.04. While conventional methods are also influential in learning to write text description in the control class. Evidenced by an increase in student value, the mean time of the mean value is 65.28. After the conventional method applied in the learning process in this class, the students' learning outcomes increase at the time of pascates with the average value () 75.68. Based on the test results concluded that there is a significant difference between the results of learning to write a description text between cooperative learning methods jigsaw model with conventional methods. This is seen in the comparison of tcount with ttable (3.290> 2.021), because tcount is bigger than ttable then Ha (Alternative Hypothesis) is accepted. Thus, the learning result of the experimental class students taught by cooperative learning method of jigsaw model is better than the learning result of the control class students taught by conventional method.